A numerical procedure and coupled system formulation for the adjoint approach in hyperbolic PDE-constrained optimization problems. (15th January 2019) - Montecinos, Gino I; López-Ríos, Juan C; Ortega, Jaime H; Lecaros, Rodrigo
Abstract: The present paper aims at providing a numerical strategy to deal with Partial Differential Equation(PDE)-constrained optimization problems solved with the adjoint method. It is done throughout a coupled system formulation of the constraint PDE and the adjoint model. The resulting model is a non-conservative hyperbolic system and thus a finite volume scheme is proposed to solve it. In this form, the scheme sets in a single frame both constraint PDE and adjoint model. The forward and backward evolutions are controlled by a single parameter $η $ and a stable time step is obtained only once at each optimization iteration. The methodology requires the complete eigenstructure of the system as well as the gradient of the cost functional. Numerical tests evidence the applicability of the present technique.